Study of the physic-chemical and mineromedicinal quality of thermal waters of the Baños del Inca - Maxe Malca, María Raquel (2015)
Baños del Inca is one of the more important spas of America that is find in the Cajamarca city to 6 km to east of the city. The Fuming liquid appear since the volcanic rock of subsoil which temperatures approaches 70 and 75°C, the heat of the water is of volcanic origin. The present investigation has as purpose to determine the physical properties and chemical composition of water, of Baños del Inca: Cajamarca using methods recognized of drinking waters and waste waters for to know its composition and to identify possible therapeutic properties. The physical chemical analysis were produced: temperature, pH, total dissolved solids, electrical conductivity, saltiness, bicarbonate, chlorides, sulfates, sulphides, sodium, total hardness and calcium hardness; moreover of fixed metals and dissolved metals. They were used standardized methods, among them, of APHA, AWWA, WPCF. The results show the physical properties and chemical composition with an average temperature of 72, 1 °C that according the temperature allows considering these waters as hyper thermals; presents characteristics of types oligomineral of medium mineralization which it’s characterized for presenting a variety of ions importants. The predominant ion of these waters is the sulphate anion, which presented concentrations for above the rest of the ions analyzed, follows of bicarbonates and the sodium. From the results it emerges that these waters are not suitable for the food and agricultural, they are medicinal waters recommendable in rheumatic affections and locomotor system process that request of Rehabilitation Hydrotherapy besides showcasing sedative and relaxing effects.